Acute lower limb ischemia and intestinal necrosis due to arterial tumor embolism from advanced lung cancer: a case report and literature review - Sayuri Togo; Terutoshi Yamaoka; Kazutoyo Morita; Kazuomi Iwasa; Yukihiko Aoyagi; Yumi Oshiro; Takatoshi Fujishita; Hideki Yokoyama; Takashi Matsui; Takashi Nishizaki (Surgical Case Reports, 2018)
Abstract Background Arterial tumor embolism (ATE) is a rare but life-threating complication. Presentation of case A 55-year-old man with acute lower-limb ischemia was referred to our hospital after endovascular intervention failed and underwent above-the-knee amputation for severe limb necrosis. On postoperative day 8, he developed small bowel necrosis and underwent resection. Histopathological examination of the resected bowel revealed that the submucosal arterial emboli were positive for the markers of squamous cells. He had unresectable lung squamous cell carcinoma with left atrium invasion. The subsequent embolisms were thought to be caused by the advanced lung cancer. Conclusion ATE is rare but should be considered as a differential diagnosis for unidentified arterial occlusion.